2023
DOI: 10.3390/v15020446
|View full text |Cite
|
Sign up to set email alerts
|

Association between SARS-CoV-2 Viral Load and Patient Symptoms and Clinical Outcomes Using Droplet Digital PCR

Abstract: The association between nasopharyngeal (NP) SARS-CoV-2 viral loads and clinical outcomes remains debated. Here, we examined the factors that might predict the NP viral load and the role of the viral load as a predictor of clinical outcomes. A convenience sample of 955 positive remnant NP swab eluent samples collected during routine care between 18 November 2020 and 26 September 2021 was cataloged and a chart review was performed. For non-duplicate samples with available demographic and clinical data (i.e., non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(113 reference statements)
1
3
0
Order By: Relevance
“…Consistent with studies of other variants, our results also suggested that the viral loads in Omicron infection had a clear relationship with the outcomes of hospitalised patients [ 22 , 35 ]. Of all participants, 10 patients eventually died, and more than half of them had an initial △Ct value less than zero.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with studies of other variants, our results also suggested that the viral loads in Omicron infection had a clear relationship with the outcomes of hospitalised patients [ 22 , 35 ]. Of all participants, 10 patients eventually died, and more than half of them had an initial △Ct value less than zero.…”
Section: Discussionsupporting
confidence: 90%
“…Both kits appeared not able to detect positive samples with lower viral loads (Cycle threshold > 30). Considering that individuals with fever and respiratory symptoms showed higher nasopharyngeal SARS-CoV-2 viral loads in terms both of digital PCR (Viral load quantification) and qPCR (Ct values) than those without those symptoms [18,19], the antigenic tests abovementioned might provide a useful assay to screen symptomatic patients in critical settings. Moreover, the possibility to use the same instrument to read results obtained by both kits may provide the ability to rapidly switch between them according to the pandemic context (i.e., presence or absence of contemporary Flu peak and increase in SARS-CoV-2 infection) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Remnant samples were analyzed using digital PCR (dPCR). Full details of the analysis can be found in Hastie et al [ 20 ] and in the Supplementary Material. In brief, RNA was extracted from 140 μL of the UTM, and eluted from the QIAgen column with 60 μL of Buffer AVE. 1 μL of the RNA extraction was loaded into a reaction mix, droplets were generated using the BioRad QX200 Droplet Generator, and PCR was run overnight using BioRad's C1000 Touch thermal cycler.…”
Section: Introductionmentioning
confidence: 99%